Coasts in Peril? A Shoreline Health Perspective - Cooper, J. A. G.; Jackson, Derek W. T. (Frontiers in Earth Science, 2019)
Most assessments of coastal vulnerability are undertaken from the perspective of the risk posed to humans, their property and activities. This anthropocentric view is based on widespread public perception (a) that coastal change is primarily a hazard to property and infrastructure and (b) that sea defences (whether soft or hard) are required to mitigate and eliminate coastal hazards. From the perspective of coastal ecosystems such a view is both perverse and damaging. In this paper we present an alternative approach to coastal assessment that centres on the physical integrity of the coast and its associated ecosystems both now and in the near-future. The shoreline health approach represents a new paradigm for coastal management and is intended to provide a much-needed ecosystem perspective. Its premise is to categorize coasts on the degree to which their ability to function morphodynamically has been compromised by human intervention. We present an expert assessment approach involving five categories that range from “Good Heath” (with “Heath Warning” and “Minor Wounds” sub-divisions), through “Minor Injury”, “Major Injury”, “On Life Support” to “Deceased”. We illustrate the concept using tabulated examples of each category from cliffed, clastic and delta coasts and demonstrate its utility through two applications. This approach has the potential to quantify the degree to which coastal ecosystems have been damaged and to focus attention on the cumulative impact of human activities on coastal ecosystems.